PERSONALLY FOCUSED LEARNING ON COURSES OF QUALIFICATION OF TEACHERS AS A MEANS OF CREATIVE FORMATION PERSONALITIES OF THE TEACHER - H.B. Shtelmakh (Academy of Cognitive and Natural Sciences, 2006)
The article deals with the preference of the personal and orientative teaching during the process of pedagogical training. Favourable psychological climate in any pedagogical collective is a necessary condition in forming o f creative teacher's personality.